2009
DOI: 10.3233/s12349-009-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

A nationally representative survey of hospital malnutrition: the Italian PIMAI (Project: Iatrogenic MAlnutrition in Italy) study

Abstract: Overall prevalence of malnutrition was 30.7%, with higher rates in the northern macroarea (36.7%) than in central (28.0%), southern (26.9%) and island (16.7%) ones (p < 0.0001). This discrepancy appeared to be mainly related to the prevalence of overweight/obesity. By a multivariate model, malnutrition was significantly lower in males (p < 0.05) and surgical wards (p < 0.002), associated with geography (p < 0.05) and consistently higher in patients aged ≥65 years (p < 0.01), presenting with malignancies (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The ratio of SDNC professionals to members of the population is around 1/133,000, but the heterogeneity per macro area is higher. 39 In addition, a recent nationwide survey (the PIMAI study -Project: Iatrogenic MAlnutrition in Italy) of nutritional risk at hospital admission, revealed that 51.7% of inpatients needed medical nutrition treatment at the time of hospital admission, primarily for malnutrition and obesity (21% and 30.7%, respectively). 39 Other indicators relevant to the present inadequacy of nutritional services include the following: 1) Insufficient presence of dietetic services.…”
Section: Italian National Health Care Systemmentioning
confidence: 99%
“…The ratio of SDNC professionals to members of the population is around 1/133,000, but the heterogeneity per macro area is higher. 39 In addition, a recent nationwide survey (the PIMAI study -Project: Iatrogenic MAlnutrition in Italy) of nutritional risk at hospital admission, revealed that 51.7% of inpatients needed medical nutrition treatment at the time of hospital admission, primarily for malnutrition and obesity (21% and 30.7%, respectively). 39 Other indicators relevant to the present inadequacy of nutritional services include the following: 1) Insufficient presence of dietetic services.…”
Section: Italian National Health Care Systemmentioning
confidence: 99%
“…Malnutrition in elderly inpatients hospitalized on medical wards is a significant public health concern [1] affecting up to 60-70% of this subpopulation [2,3]. Malnutrition is a wellestablished predictor of mortality in hospitalized patients [4,5].…”
Section: Introductionmentioning
confidence: 99%